Virtual reality and the role of the prefrontal cortex in adults and children. - Jäncke, Lutz; Cheetham, Marcus; Baumgartner, Thomas (Frontiers in Neuroscience, 2009)
In this review the neural underpinnings of the experience of presence are outlined. Firstly, it will be shown that presence is associated with an activation of a distributed network including the dorsal and ventral visual stream, the parietal cortex, the premotor cortex, mesial temporal areas, the brainstem and the thalamus. Second, the dorsolateral prefrontal cortex (DLPFC) is identified as a key node of this network in that it modulates the activity of this network and the associated experience of presence. Third, because of their unmatured frontal cortex, children lack the strong modulatory influence of the DLPFC on this network. Fourth, it is shown that by manipulating the activation in the DLPFC using transcranial direct current stimulation (tDCS) while participants are exposed to the virtual roller coaster ride presence-related measures are influenced. Finally, these findings are discussed in the context of current models explaining the experience of presence, the rubber hand illusion, and out of body experiences.